2022
DOI: 10.1002/lno.12155
|View full text |Cite
|
Sign up to set email alerts
|

Alkalinity export to the ocean is a major carbon sequestration mechanism in a macrotidal saltmarsh

Abstract: Saltmarshes are a blue carbon ecosystem accumulating large quantities of organic carbon in sediments. Some of this carbon can be transformed into dissolved inorganic carbon (DIC) and methane (CH 4 ) that may eventually be exported to the ocean or atmosphere. Although extensive studies have quantified specific components of the carbon budget such as carbon burial, limited attention has been given to pore-water-derived carbon and total alkalinity (TA) exports to the ocean. Here, we quantified lateral exports to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 78 publications
1
11
0
Order By: Relevance
“…This has been observed in other tidally-influenced ecosystems such as mangroves and saltmarshes where higher CH 4 concentration in porewater drives the high surface water CH 4 (Call et al, 2018;Santos et al, 2019;Yau et al, 2022). Flanking saltmarshes adjacent to seagrass export CH 4 , elevating CH 4 flux in the seagrass meadows (Al-Haj et al, 2022).…”
Section: Low Seagrass Ch 4 Emissions On Local and Global Scalesmentioning
confidence: 70%
See 2 more Smart Citations
“…This has been observed in other tidally-influenced ecosystems such as mangroves and saltmarshes where higher CH 4 concentration in porewater drives the high surface water CH 4 (Call et al, 2018;Santos et al, 2019;Yau et al, 2022). Flanking saltmarshes adjacent to seagrass export CH 4 , elevating CH 4 flux in the seagrass meadows (Al-Haj et al, 2022).…”
Section: Low Seagrass Ch 4 Emissions On Local and Global Scalesmentioning
confidence: 70%
“…Seagrass seems to emit less CH 4 than other coastal vegetated ecosystems such as mangroves and saltmarshes. For example, previous studies showed that methane emissions can offset <6% of carbon burial in a saltmarsh in China (Yau et al, 2022) and 18% in Australian mangroves receiving freshwater inputs (Rosentreter et al, 2018). Since seagrass are fully submerged and freshwater inputs are often limited, higher CH 4 oxidation in the water column could reduce CH 4 emissions relative to periodically inundated mangrove and saltmarsh systems.…”
Section: Implications For Net Carbon Sequestrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Late-stage green tides can also cause serious negative environmental impacts, such as the occurrence of hypoxia, acidification, and even the production of toxic hydrogen sulfide (H 2 S) in the nearshore areas covered by dense macroalgal fronds. , In the organic-rich hypoxic environment, total alkalinity (TAlk) can be generated through anaerobic organic matter mineralization processes (e.g., sulfate reduction and denitrification). The generation of TAlk through sulfate reduction has been found in mangrove forests, and denitrification was considered as a dominant reaction for TAlk generation in a subterranean estuary . The increase in TAlk, a key index for the capacity of seawater to store DIC, allows more DIC to remain in the seawater as bicarbonate (HCO 3 – ) rather than degas back to the atmosphere as CO 2 . Given that seawater TAlk usually increases evidently during green tides, we speculate that a substantial portion of those increased DICs may persist in seawater after green tides, potentially playing a role in inorganic carbon sequestration in the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2022) performed large-scale modeling to quantify CO 2 uptake from rivers and groundwater following weathering of carbonate and silicate rocks, thus revealing the potential contribution of enhanced rock weathering as an atmospheric CO 2 sink. Yau et al (2022) built a comprehensive saltmarsh carbon budget that showed large dissolved carbon sequestration via lateral exports. Saltmarsh alkalinity production followed by porewater-derived exports to the ocean was comparable to carbon burial in local sediments.…”
mentioning
confidence: 99%